PARTISIPASI MASYARAKAT DALAM PENGELOLAAN LUMBUNG PANGAN “SUMBER MAKMUR” GUNA MEWUJUDKAN KETAHANAN PANGAN - Kurnia Siti Afifah; Sri Wibawani (Jurnal Penelitian Administrasi Publik, 2019)
There are two research objects in this study, the first object is to find out community participation in the management of food barns then, second object is to find out the factors that influence the growth and development of community participation in the management of "Sumber Makmur" food barns to realize food security in Dusun Dander Desa Manduro Kecamatan Kabuh Kabupaten Jombang. While the object of this study is community participation in the management of "Sumber Makmur" food barns. This research is a qualitative descriptive study with a research focus based on the scope of community participation according to Yadav and the factors that influence the growth and development of community participation according to Slamet (Mardikanto: 2015). The data used in this study include primary data and secondary data, data sources obtained from informants were selected based on purposive sampling and snowball sampling. The data collection techniques used through interviews, observation, literature studies, and documentation are then analyzed using data collection, data reduction, data display, and conclusion drawing. The results showed that community participation in the management of the "Sumber Makmur" food barn included participation in decision-making, implementation of activities, monitoring and evaluation and utilization of results. In general, this participation has been optimal to achieve food security in Dusun Dander Desa Manduro Kecamatan Kabuh Kabupaten Jombang. In the second object of the study stated that the growth and development of community participation in the management of "Sumber Makmur" food barns is influenced by factors of opportunity and ability. While the willingness factor has not emerged as a mental attitude to build, because the willingness of the community to participate is more influenced by the encouragement of food and farming needs. Keyword : Community Participation, Growth And Development Factors Of Community